Assessment of Explosive Ordnance Disposal (EOD) Functions for the Effective Management of Improvised Explosive Device (IED) Threats - Manikan, Wilmer (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of Explosive Ordnance Disposal (EOD) functions in managing Improvised Explosive Device (IED) threats by assessing key operational factors influencing mission performance and organizational capability. Guided by the concepts of operational preparedness, risk management, inter-agency collaboration, and technological support, the study utilized a quantitative descriptive-correlational research design. Data were gathered using validated survey questionnaires administered to selected respondents directly involved in EOD operations. Statistical tools such as frequency counts, weighted mean, and correlation analysis were employed to determine the level of effectiveness of EOD functions and the relationships among operational variables. Findings revealed that training and expertise, advanced technology utilization, inter-agency coordination, organizational resource allocation, and risk assessment and mitigation significantly contribute to the effectiveness of EOD operations in addressing IED threats. The study showed that competent personnel, sufficient logistical and technological resources, coordinated institutional responses, and systematic risk management enhance operational readiness, response capability, and mission success. Results further established significant relationships between these operational factors and overall EOD effectiveness, indicating the importance of strengthening institutional capability and preparedness in responding to increasingly complex security threats. The study concluded that enhancing personnel competence, improving technological modernization, reinforcing inter-agency coordination, and sustaining comprehensive risk mitigation practices are essential for effective EOD operations. Consequently, the study recommended continuous specialized training, adequate resource allocation, technological upgrades, and strengthened collaborative operational frameworks to improve mission efficiency and personnel safety. The study supports Sustainable Development Goal (SDG) 16, which promotes peace, justice, and strong institutions through improved public safety and security mechanisms. It also contributes to SDG 9 by emphasizing technological innovation and institutional capability enhancement in security operations. The sustainability impact of the study lies in strengthening institutional resilience, improving operational governance, and supporting safer communities through effective threat management and coordinated security responses.